Trapped in the House: Internet Use and Loneliness in Students during the COVID-19 Pandemic - Hendro Prabowo; Mahargyantari Purwani Dewi; Nur Aziz Afandi; Henny Regina Salve; Astri Nur Kusumastuti; Dinar Sari Eka Dewi (UM Purwokerto Press, 2021)
People in the world, including students, in social isolation during the Coronavirus pandemic, must stay at home, separate themselves from others and implement health protocols. As a consequence, university students must learn from home and distance learning online. This study aims to find the link between internet use and loneliness in 620 students in several cities in Java and Sumatra. The results showed the average internet usage was 10 hours per day, and the average nightly sleep was 6.5 hours per day, the average nap or nap was 1.3 hours per day. There is a very significant relationship between loneliness and online activity.